An improved method for detecting telomere size differences in T-lymphocyte interphases from older people with Down syndrome with and without mild cognitive impairment. Issue 1 (4th May 2017) - Jenkins, E. C.; Ye, L.; Marchi, E.; Krinsky-McHale, S. J.; Zigman, W. B.; Schupf, N.; Silverman, W. P.
Abstract: Telomere size (quantified by fluorescence intensity and physical lengths) in short-term T-lymphocyte cultures from adults with Down syndrome (DS) with and without mild cognitive impairment (MCI-DS) or dementia was compared. For these studies, dementia status was determined based on longitudinal assessments employing a battery of cognitive and functional assessments developed to distinguish adult-onset impairment from preexisting developmental disability. In the course of our studies using a MetaSystems Image Analyzer in combination with ISIS software and a Zeiss Axioskop 2, we found that Fluorescein isothiocyanate (FITC) telomere fluorescence referenced to chromosome 2-identified FITC probe fluorescence as a nontelomere standard (telomere/cen2 ratio) showed great promise as a biomarker of early decline associated with Alzheimer's disease (AD) in this high-risk population. We have now obtained a cen (2) CY3 probe that can clearly be distinguished from the blue–green FITC interphase telomere probe, providing a clear distinction between telomere and centromere fluorescence in both interphase and metaphase. We used FITC/CY3 light intensity ratios to compare telomere length in interphases in adults with DS with and without MCI-DS or dementia. Five age-matched female and five age-matched male pairs ( n = 10) all showed clear evidence of telomere shortening associated with clinical progression of AD ( P < 0.002 – P < 0.000001), with distributions of mean values for cases and controls showing no overlap. We also examined the time needed for microscopy using interphase versus metaphase fluorescence preparations. With interphase preparations, examination time was reduced by an order of magnitude compared with metaphase preparations, indicating that the methods employed herein have considerable practical promise for translation into broad diagnostic practice.